(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the clinical management of patients with Robin Sequence by their caregivers at home. Method: This is an exploratory-descriptive research, with quantitative and qualitative data analysis, developed with caregivers of patients with Robin Sequence treated at a specialized care center for patients with craniofacial anomalies located in western Paraná. Data collection was carried out in June and July 2022, through individualized interviews. The findings were submitted to content analysis. Results and discussions: All caregivers interviewed were mothers of patients with Robin Sequence. Most were between 20 and 40 years old, had higher education and had no formal job. None of the patients had associated syndromes and all were from the western macro-region of Paraná. Nasopharyngeal cannula and nasogastric tube were the two types of invasive devices used by patients, and most patients did not use any invasive device. The respondents’ responses were analyzed and grouped into four response categories, namely: Physiological Aspects, Psychological Aspects, Economic Aspects and Spiritual Aspects. Conclusion: Knowing aspects related to the care of patients with Robin Sequence at home supports decision-making and the choice of assertive actions by the health team.